THE EFFECTIVENESS OF FUZZY LOGIC CONTROL FOR PV PUMPING SYSTEM - TERKI, A.; MOUSSI, A.; BETKA, A.; TERKI, N. (Courrier du Savoir; Vol. 12 (2012): Courrier du Savoir)
This paper presents an optimal operation of a photovoltaic pumping system. An analysis by witch the dynamic performances of a permanent magnet brushless DC (PMBLDC) motor is controlled through a hysteresis current loop and an outer speed loop with different controllers. The dynamics of the drive system with (PI) and a Fuzzy logic (FL) speed controllers are presented. In order to optimize the overall system efficiency, a maximum power point tracker is also used. Simulation is carried out by formatting the mathematical model for photovoltaic source, MPPT, motor and pump load. The results with FL speed controller show improvement in transient response of PMBLDC drive over conventional PI. The effectiveness of the FL controller is also demonstrated.